VISUALISATION OF 4D THERMAL MAPS - Gorazd Hren (Journal of Energy Technology, 2025)
Today, there are many building energy simulation systems. Most rely on theoretical thermal models and numerical simulations to improve the building design and achieve good energy-efficient living conditions. The 3D visualisation technique proposed in this paper analyses temperature distribution in a room. A room is divided into uniform grids, and the temperature field is established by calculating temperature values for each cell using an inverse distance weighted interpolation algorithm with sensor data. These cells are visualised by voxel rendering. An X3D simulation system coupled with a cost-effective set of temperature sensors can provide valuable insights into room design. A measured thermal status can lead to energy savings and improved thermal comfort with improved efficiency. The paper discusses the cost-effective and simplified process for a hardware-software prototype system that can provide real data-driven 4D thermal maps for buildings. The system can be extended to provide 4D thermal maps for more rooms and multi-storey buildings.